2018
DOI: 10.3389/fimmu.2018.00307
|View full text |Cite
|
Sign up to set email alerts
|

Signals Controlling Lytic Granule Polarization at the Cytotoxic Immune Synapse

Abstract: Cytotoxic immunity relies on specialized effector T cells, the cytotoxic T cells, which are endowed with specialized cytolytic machinery that permits them to induce death of their targets. Upon recognition of a target cell, cytotoxic T cells form a lytic immune synapse and by docking the microtubule-organizing center at the synaptic membrane get prepared to deliver a lethal hit of enzymes contained in lytic granules. New insights suggest that the directionality of lytic granule trafficking along the microtubul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 152 publications
(203 reference statements)
0
37
0
Order By: Relevance
“…ZAP70 phosphorylates LAT which recruits SLP76 which in turn is phosphorylated by ZAP70 to result in the LAT-SLP76 signalosome. One of the most important signaling effectors of the LAT-SLP 76 signalosome is phospholipase C (PLC) which transduces the TCR signal by hydrolyzing phosphatidyl (4,5) bisphosphate into IP3 and DAG. The local DAG gradient promotes recruitment of PKC isoforms which mediate signaling inducing MTOC polarization and synapse polarity [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ZAP70 phosphorylates LAT which recruits SLP76 which in turn is phosphorylated by ZAP70 to result in the LAT-SLP76 signalosome. One of the most important signaling effectors of the LAT-SLP 76 signalosome is phospholipase C (PLC) which transduces the TCR signal by hydrolyzing phosphatidyl (4,5) bisphosphate into IP3 and DAG. The local DAG gradient promotes recruitment of PKC isoforms which mediate signaling inducing MTOC polarization and synapse polarity [2].…”
Section: Introductionmentioning
confidence: 99%
“…IS formation results in visible morphological modifications occurring due to changes in the composition and density of molecules such as central actin depletion, recycling TCR polarization, cytotoxic granule (CG) polarization [4]. Initial triggering of the TCR leads to formation of numerous TCR micro-clusters whose structure resembles a miniature synapse in that every TCR micro-cluster is surrounded by a micro-ring containing adhesion molecules.…”
Section: Introductionmentioning
confidence: 99%
“…However, this resulting polarization of cytotoxic granules, transfer of granzymes into target cells and induction of apoptosis can be the consequence of either the spatial clustering of the NK regulatory receptors at the CD56-mediated interaction between NK-92 and target cells thereby increasing the efficacy of intracellular signaling 11,12 or the direct CD56-mediated regulation of signaling pathways that control lytic granule polarization at the immune synapse. Although the role of CD56 in the latter process was not previously described, CD56 is known to regulate molecules such as fyn that are essential for promoting lytic granule polarization to the lytic synapse 40,62 . Furthermore, comparison of the differential gene expression of all known-to-date ligands for NK regulatory receptors 63 between the different NK-92-sensitive and resistant breast precancerous and cancerous cell lines showed that three ligands CD70, CD72 and COL3A1 have an expression profile comparable to that of CD56 (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The precision in killing is ensured by polarized secretion of the cytotoxic granules toward the immune synapse [reviewed in (136)(137)(138)(139)]. The polarization depends on the phospholipase C-g and Ca 2+ -dependent signaling of the TCR or NK activating receptors and is followed by dynein-dependent movement and docking of the microtubule organizing center at the synapse.…”
Section: Perforin-1 Is Released From Cytotoxic Granules Into a Neutramentioning
confidence: 99%